2014
DOI: 10.1002/ijc.28939
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dendritic cell-targeting lipopeptide as an immunoadjuvant that inhibits tumor growth without inducing local inflammation

Abstract: Materials used for the past 30 years as immunoadjuvants induce suboptimal antitumor immune responses and often cause undesirable local inflammation. Some bacterial lipopeptides that act as Toll-like receptor (TLR) 2 ligands activate immune cells as immunoadjuvants and induce antitumor effects. Here, we developed a new dendritic cell (DC)-targeting lipopeptide, h11c (P2C-ATPEDNGRSFS), which uses the CD11c-binding sequence of intracellular adhesion molecule-1 to selectively and efficiently activate DCs but not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 46 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…Upon encounter with specific microbial molecules TLR receptor are activated and initiate downstream signaling via MyD88-dependent or -independent pathways [41]. The identification of TLRs advanced the field of immunoadjuvants greatly, as most microbial immunoadjuvants work through TLR ligands [30], [42, 43]. Thus by controlling most TLRs as well as professional APCs, gp96 modulates both the innate and adaptive components of the immune system.…”
Section: Gp96 Cancer-associated Clientelementioning
confidence: 99%
See 1 more Smart Citation
“…Upon encounter with specific microbial molecules TLR receptor are activated and initiate downstream signaling via MyD88-dependent or -independent pathways [41]. The identification of TLRs advanced the field of immunoadjuvants greatly, as most microbial immunoadjuvants work through TLR ligands [30], [42, 43]. Thus by controlling most TLRs as well as professional APCs, gp96 modulates both the innate and adaptive components of the immune system.…”
Section: Gp96 Cancer-associated Clientelementioning
confidence: 99%
“…Moreover, current work utilizing genetic knockout (KO) strategies have revealed exciting cell-intrinsic roles of gp96 in innate immunity, inflammation, cytoprotection, development, stemness and oncogenesis [5, 18, 3032]. This review will mainly focus on the cell-intrinsic roles of gp96 in cancer development, as the basic aspects of gp96 ER function such as calcium homeostasis, mechanisms of protein folding and quality control have already been reviewed extensively elsewhere [33, 34].…”
Section: Gp96 and Cancer: Introductionmentioning
confidence: 99%
“…Designing of new adjuvants based on the structure of MALP-2 is also under way [11,36]. Our data revealed that NK cells are indirectly affected by MALP-2.…”
Section: Discussionmentioning
confidence: 76%
“…The following peptides and lipopeptides (purity >90%) were customized by Bio‐Synthesis (Lewisville, TX, USA) via Biologica (Nagoya, Aichi, Japan): OVA peptide, SIINFEKL; murine WT1 peptide, RMFPNAPYL; bio‐SK4 peptide, biotinylated‐SKKKK; bio‐MALP2 peptide, biotinylated‐GNNDESNISFKEK; bio‐SR11 peptide, biotinylated‐SRRRRRRRRRRR; bio‐SK11 peptide, biotinylated‐SKKKKKKKKKKK; P2CSK4 lipopeptide, P2C‐SKKKK; MALP2 lipopeptide, P2C‐GNNDESNISFKEK; P2CSR11 lipopeptide, P2C‐SRRRRRRRRRRR; and P2CSK11 lipopeptide, P2C‐SKKKKKKKKKKK.…”
Section: Methodsmentioning
confidence: 99%
“…When we examine the effects of vaccines after removal of free lipopeptide, the BMTC were administered twice intradermally. A lipopeptide dose of 10 nmol was validated previously using P2CSK4 as a positive control . An anti‐mouse PD‐L1 antibody (InVivoMab; 10F.9G2, Bio X Cell, West Lebanon, NH, USA; 200 μg per mouse) was injected intraperitoneally on the same day as the BMTC.…”
Section: Methodsmentioning
confidence: 99%